Insecticidal effect of some spices on Callosobruchus maculatus (Fabricius) in black gram seeds (University Journal of Zoology, Rajshahi University, 2009)
The experiment was conducted to investigate the insecticidal potency of some spices eg. clove (Syzygium aromaticum), black pepper (Piper nigrum), ceylon cinnamon (Cinnamomum zeylanicum), black cardamom (Amomum subulatum), nutmeg (Myristica fragnans), black cumin (Nigella sativa), turmeric (Curcuma longa), red pepper (Capsicum frutescens), cumin (Cuminum cyminum), green cardamom (Elettaria cardamomum) and bay leaf (Cinnamomum tamala), against the pulse beetle, Callosobruchus maculatus (F.) on stored black gram (Phaseolus bengalensis L.). Data were recorded on days to 100% mortality; number of adults emerged and weight loss (%) of black gram. All the spices were effective as protectants of black gram seeds. However, clove and black pepper were most effective. Key words: Callosobruchus maculatus, stored black gram, mortality, adult emerge, extent of damage. doi:10.3329/ujzru.v27i0.1953 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 47-50